Иванушка Первый, или Время чародея: [повесть] / Карен Арутюнянц - Арутюнянц Карен Давидович (Современная проза, 2016)
Экземпляры: (20170921) / Инвентарный номер: 49792 / Цена: 312.00 / Авт.знак: А 86 / ББК: 84(2=411.2)6